Hubungan Tingkat Pengetahuan Tentang Covid-19 dengan Tingkat Kecemasan pada Lansia di Kelurahan Jebres - Isnaini Nur Faatihah; Norman Wijaya Gati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Coronavirus Disease as known as Covid-19 is an infectious disease caused by Sars Cov-2. Covid-19 can be transmitted in direct through saliva, droplets, and bad air.The prevalence of Covid-19 cases in the elderly in Indonesia the age range of ≥60 years, which is 47.3% of cases and the number of elderly deaths due to Covid-19 is 15,023 people. The decline of the immune system in elderly can increase the risk of Covid-19, even to death. One of the effect of Covis-19 is psychological disorders of anxiety. To know relationship between levels of knowledge of covid-19 and levels of anxiety among elderly at kelurahan jebres. The design of this research used quantitative and analytical cross sectional study design, and the number of samples was determined using Slovin’s formula, there are 98 respondents. Data results were analyzed using statistical software with a Spearman Rank test. The results showed that relation between level of knowledge of Covid-19 and level of anxiety among elderly at Kelurahan Jebres was found (p-value = 0,001 (p<0,05)). So, there was relation observed between the level of knowledge and level of anxiety. Data results showed that the level of knowledge about Covid-19 is classified good (54,1%) and the level of anxiety is mild anxiety (58,2%). There is a relationship between level of knowledge of Covid-19 and level of anxiety among elderly at Kelurahan Jebres.